2021
DOI: 10.14434/josotl.v21i1.30290
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and Assessing Undergraduate Research Campus-wide: Demographics, Academic Success, and Post-Graduation Plans

Abstract: Evaluation must occur at the university level to understand the full impact of undergraduate research (UR). UR assessment is often only completed at the individual program level because of limited technology, time, and/or resources. At our large research institution, we have been documenting a wide variety of research experiences annually since the 2009–2010 academic year through an online portal. With our institutional research team and campus partners, we created interactive dashboards that display involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…1, April 2023. josotl.indiana.edu et al (2022) found that engagement in undergraduate research of different research modalities (all cocurricular) at a Hispanic-Serving Institution (HSI) is associated with increased number of successfully completed semester credit hours, higher GPAs, increased graduation rates, and higher enrollment in further education. Schneider et al (2021) showed similar trends of students engaged in UGR having demonstrated increased GPAs as well as entry into graduate school. Schneider et al (2021) also identified a gap in the literature by stating "We have not looked at this data regarding how many 'times' students appeared in our database, but that would warrant further investigation to see if extended involvement impacted GPA (and other factors)."…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…1, April 2023. josotl.indiana.edu et al (2022) found that engagement in undergraduate research of different research modalities (all cocurricular) at a Hispanic-Serving Institution (HSI) is associated with increased number of successfully completed semester credit hours, higher GPAs, increased graduation rates, and higher enrollment in further education. Schneider et al (2021) showed similar trends of students engaged in UGR having demonstrated increased GPAs as well as entry into graduate school. Schneider et al (2021) also identified a gap in the literature by stating "We have not looked at this data regarding how many 'times' students appeared in our database, but that would warrant further investigation to see if extended involvement impacted GPA (and other factors)."…”
mentioning
confidence: 65%
“…Schneider et al (2021) also identified a gap in the literature by stating "We have not looked at this data regarding how many 'times' students appeared in our database, but that would warrant further investigation to see if extended involvement impacted GPA (and other factors)." They also identified only a small difference between their institutional and UGR population in terms of years to degree completion, indicating that UGR students have not graduated in fewer semesters than the university undergraduate population, and further suggesting that "it would be interesting to know if other campuses see similar trends" (Schneider et al, 2021). This paper aims to address these gaps in the literature.…”
mentioning
confidence: 98%
“…Gathering and analyzing data on the different types of UREs for students is needed to help researchers better understand whether these UREs are accessible and welcoming to students from varying backgrounds. When assessing undergraduate research programs, Schneider et al (2021) found that this information is limited due to technology, time, and/or resources of individual programs. By shedding light on the gaps in support, this research can reveal the deficiencies in services provided to first-generation, underrepresented, nontraditional, and socioeconomically disadvantaged students.…”
Section: Limitationsmentioning
confidence: 99%